Togo - 2015 - Dirk Kohnert (Africa Yearbook Volume 12: Politics, Economy and Society South of the Sahara in 2015, 2016)
The presidential elections of 25 April 2015 resulted in a victory for the incumbent, Faure Gnassingbé. Thus, he secured his third five-year term, strengthening the autocratic grip of the Gnassingbé-clan, which had been in power since 1967. The institutional and constitutional reforms that would have been required for free and fair elections and which the opposition parties, civil society and international donors demanded, were postponed indefinitely. Nevertheless, the international community declared the elections free and fair, given their security interests in the region. Economic growth remained stable at about 5% p.a., although economic growth rates were not inclusive and benefitted the few. The business climate improved considerably. – – Die Präsidentschaftswahlen vom 25. April 2015 endeten mit einem Sieg für den amtierenden Präsidenten Faure Gnassingbé. Damit sicherte er sich seine dritte fünfjährige Amtszeit und festigte den autokratischen Griff des Gnassingbé-Clans, der seit 1967 an der Macht war. Die institutionellen und verfassungsmäßigen Reformen, die für freie und faire Wahlen erforderlich gewesen wären und die von den Oppositionsparteien, der Zivilgesellschaft und den internationalen Geldgebern gefordert wurden, wurden auf unbestimmte Zeit verschoben. Dennoch erklärte die internationale Gemeinschaft die Wahlen angesichts ihrer Sicherheitsinteressen in der Region für frei und fair. Das Wirtschaftswachstum blieb mit etwa 5 % p.a. stabil, obwohl die Wirtschaftswachstumsraten nicht inklusiv waren und nur Wenige begünstigten. Das Geschäftsklima verbesserte sich erheblich.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2015; domestic policy; foreign affairs; socio-economic development; period under review 2015